1995
DOI: 10.1007/bf02208670
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fatty liver in Japanese children and relationship to obesity

Abstract: The prevalence of fatty liver in children is unknown and its relationship to obesity is poorly defined. The present study of 810 northern Japanese children (4-12 years old) determined the prevalence of fatty liver in the pediatric population and its relationship to obesity. Diagnosis of fatty liver was based on established real-time ultrasonographic criteria. The overall prevalence of fatty liver was 2.6% and was higher for boys (3.4%) than for girls (1.8%), although not statistically significant (P = 0.15). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
253
3
13

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 385 publications
(278 citation statements)
references
References 32 publications
9
253
3
13
Order By: Relevance
“…Among the entire pediatric population enrolled in this study, the prevalence of mild-serious NAFLD (score C 1) was 4.4%, with a prevalence of 6.6% in males and 2.0% in females. This result confirms the existence of a gender difference in the prevalence of NAFLD, which has also been shown in previous studies [2,9].…”
Section: Prevalence Of Pediatric Nafldsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the entire pediatric population enrolled in this study, the prevalence of mild-serious NAFLD (score C 1) was 4.4%, with a prevalence of 6.6% in males and 2.0% in females. This result confirms the existence of a gender difference in the prevalence of NAFLD, which has also been shown in previous studies [2,9].…”
Section: Prevalence Of Pediatric Nafldsupporting
confidence: 92%
“…Rashid et al [7] reported cirrhosis in children as young as 10 years. Although results from population-based epidemiologic studies are limited, the prevalence of NAFLD seems to be higher than expected [8], and an earlier epidemiological survey carried out by our group found the prevalence of this condition among school children (4-12 years of age), as detected by ultrasonography, to be 2.6%, increasing to 22.5% among obese children [9].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…The physical health of obese children is compromised in a manner similar to adults. Childhood obesity is associated with an increased risk of hyperinsulinemia, 3 insulinresistance, 4 type 2 diabetes, 5,6 hypertension, 7,8 hypercholesterolemia, 3 chronic inflammation, 9 abnormalities in endothelial function, 10 hyperandrogenemia, 4 gallstones, 11 hepatitis, 12,13 asthma, cancer 14 and orthopedic problems. 10 Obesity has also been shown to diminish children's quality of life severely 14 and is associated with decreased selfesteem 15,16 and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Measurement of abdominal subcutaneous fat thickness by ultrasonography could be a good estimate for liver involvement, especially in obese subjects. [19][20][21][22][23] Population-based approaches by this method, suggests an overall prevalence of at least 3% for suspected fatty liver disease among children and adolescents in the United States and Asia. 9,17 The histology of the liver, the most important criterion for diagnosis is usually not being used for screening.…”
Section: Introductionmentioning
confidence: 99%